OxeR1 regulates angiotensin II and cAMP-stimulated steroid production in human H295R adrenocortical cells - Dattilo, Melina Andrea (2015)
Hormone-regulated steroidogenesis and StAR protein induction involve the action of lipoxygenated products. The products of 5-lipoxygenase act on inflammation and immunity by stimulation of a membrane receptor called OxeR1. The presence of OxeR1 in other systems has not been described up to date and little is known about its mechanism of action and other functions. In this context, the aim of this study was the identification and characterization of OxeR1 as a mediator of cAMP-dependent and independent pathways. Overexpression of OxeR1 in MA-10 Leydig cells increased cAMP-dependent progesterone production. Angiotensin II and cAMP stimulation of adrenocortical human H295R cells produced an increase in StAR protein induction and steroidogenesis in cells overexpressing OxeR1 as compared to mock-transfected cells. Additionally, activation of OxeR1 caused a time-dependent increase in ERK1/2 phosphorylation. In summary, membrane receptor OxeR1 is involved in StAR protein induction and activation of steroidogenesis triggered by cAMP or angiotensin II, acting, at least in part, through ERK1/2 activation.